Self‐Assembling Nanofibers Inhibit Inflammation in a Murine Model of Crohn's‐Disease‐Like Ileitis. Issue 4 (5th February 2021) - Bury, Matthew I.; Fuller, Natalie J.; Clemons, Tristan D.; Sturm, Renea M.; Morrison, Christopher D.; Lisy‐Snow, Devon C.; Nolan, Bonnie G.; Tarczynski, Christopher; Ayello, Emily M. T.; Boyce, Amber; Muckian, Bridget; Ahmad, Nida; et al.
Abstract: Inflammatory bowel diseases are characterized by chronic inflammation, leading to the destruction of gastrointestinal tract tissue. Strategies specifically utilized to manage intestinal inflammation in patients afflicted with Crohn's disease (CD) are met with numerous obstacles. These include treatment‐specific physiological side effects and the development of resistance to biological and pharmacological therapies. As an alternative treatment approach, high aspect ratio supramolecular anti‐inflammatory peptide amphiphiles (AIF‐PAs) are engineered to mitigate small intestinal inflammation within the established, preclinical CD‐like ilieitis senescence accelerated mouse (SAMP1)/YitFcsJ murine model. Data derived from this study demonstrate ileitis that the direct injection of AIF‐PAs into inflammatory small intestinal skip lesions minimizes pathologic change in tissue architecture and intestinal physiology. When compared to untreated or saline injected control animals, AIF‐PAs substantially reduce lesion size and tissue‐specific inflammation, inciting cytokines tumor necrosis factor alpha (TNFα), interferon gamma (IFNγ), interleukin (IL)‐1β, and IL‐13 along with a concomitant decrease including in tissue proinflammatory innate and adaptive immune cells. Finally, this is accompanied by increased small bowel intestinal transit that aligns with improved gross intestinal pathology scoring. Taken together, this study provides evidence that AIF‐PAs may serve as a novel stand‐alone or combinatorial therapy to enhance efficacy in order to treat localized intestinal inflammation related to CD. Abstract : Treatment regimens for intestinal inflammation observed in Crohn's disease vary based upon disease severity and exhibit varying efficacy and multiple side effects. Patients often become refractory to treatment and typically require surgical intervention to remove highly inflamed tissue. The treatment of inflammatory intestinal lesions with self‐assembling anti‐inflammatory nanofibers can positively modulate the inflammatory milieu and restore physiological normalcy.